STATUS ANAK LUAR NIKAH DALAM KEWARISAN PASCA KELUARNYA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 - Muhammad Zul Figgar; Faisal Saidi (Al-Mizan (e-Journal), 2022)
This study aims to present the discourse on the Constitutional Court Decision Number 46/PUU-VIII/2010 concerning Law Number 1 of 1s974 concerning Marriage in the context of inheriting children outside of marriage. At the same time, this paper tries to contextualize the problems that arise from Constitutional Court Decision Number 46/PUU-VIII/2010. The method used in this paper is entirely based on literature research without neglecting the existing judge's decisions related to the context of the discussion (jurisprudence) and then analyzed descriptively qualitatively. The results of the study show that Constitutional Court Decision Number 46/PUU-VIII/2010 is a breakthrough in the renewal of marriage law in Indonesia. The Constitutional Court's decision in favor of a child outside of marriage is a middle ground in the debate about how far the status of a child outside of marriage is by the child's inheritance rights. Meanwhile, to a certain extent, the Compilation of Islamic Law (KHI) can also be used as a mitigation tool to ensure that Muslims as a whole are far from adultery and never have sexual intercourse before a legal marriage has taken place.